PENERAPAN E-GOVERNMENT MELALUI APLIKASI SI POLGAN DI DESA KRANDEGAN KABUPATEN PURWOREJO - Sri Mahardika, Sofia; Hanani, Retna; Kismartini, Kismartini (Journal of Public Policy and Management Review, 2024)
The village of Krandegan is a pioneer of digital villages that implements e-government as an innovation in public services through the Si Polgan application. (Sistem Informasi dan Pelayanan Online di Desa Krandegan). The Si Polgan application has made Krandegan Village the only village in Purworejo Regency with an e-government product in the form of an application. However, since the initial implementation of the Si Polgan Application until now, several issues have been identified, including: there are still letter services that cannot be carried out online, limited financial resources, insufficient supporting facilities and infrastructure, and a 2 lack of available human resources. This research aims to analyze the implementation of e- government through the Si Polgan Application and to identify the supporting and inhibiting factors in its implementation in Krandegan Village. The research method used is a qualitative descriptive method utilizing primary and secondary data sources. The research results indicate that the implementation of e-government through the Si Polgan Application in Krandegan Village has not yet been carried out in accordance with the two indicators of e-government implementation, namely the indicators of application provision and development, and the indicators of human resource development. Supporting factors identified in the implementation of the Si Polgan Application are found in the support and value factors, while the inhibiting factor identified in the implementation of the Si Polgan Application lies in the capacity factor, specifically the lack of human resources, financial resources, and technological infrastructure.